Oxidized Phosphatidylcholines Trigger TRPA1 and Ryanodine Receptor–dependent Airway Smooth Muscle Contraction - Vaghasiya, Jignesh; Dalvand, Azadeh; Sikarwar, Anurag; Mangat, Divleen; Ragheb, Mirna; Kowatsch, Katarina; Pandey, Dheerendra; Hosseini, Seyed Mojtaba; Hackett, Tillie L.; Karimi-Abdolrezaee, Soheila; Ravandi, Amir; Pascoe, Christopher D.; et al. (American journal of respiratory cell and molecular biology, 2023)
Asthma pathobiology includes oxidative stress that modifies cell membranes and extracellular phospholipids. Oxidized phosphatidylcholines (OxPCs) in lung lavage from allergen-challenged human participants correlate with airway hyperresponsiveness and induce bronchial narrowing in murine thin-cut lung slices. OxPCs activate many signaling pathways, but mechanisms for these responses are unclear. We hypothesize that OxPCs stimulate intracellular free Ca flux to trigger airway smooth muscle contraction. Intracellular Ca flux was assessed in Fura-2-loaded, cultured human airway smooth muscle cells. Oxidized 1-palmitoyl-2-arachidonoyl- -glycero-3-phosphocholine (OxPAPC) induced an approximately threefold increase in 20 kD myosin light chain phosphorylation. This correlated with a rapid peak in intracellular cytoplasmic Ca concentration ([Ca ] ) (143 nM) and a sustained plateau that included slow oscillations in [Ca ] . Sustained [Ca ] elevation was ablated in Ca -free buffer and by TRPA1 inhibition. Conversely, OxPAPC-induced peak [Ca ] was unaffected in Ca -free buffer, by TRPA1 inhibition, or by inositol 1,4,5-triphosphate receptor inhibition. Peak [Ca ] was ablated by pharmacologic inhibition of ryanodine receptor (RyR) Ca release from the sarcoplasmic reticulum. Inhibiting the upstream RyR activator cyclic adenosine diphosphate ribose with 8-bromo-cyclic adenosine diphosphate ribose was sufficient to abolish OxPAPC-induced cytoplasmic Ca flux. OxPAPC induced ∼15% bronchial narrowing in thin-cut lung slices that could be prevented by pharmacologic inhibition of either TRPA1 or RyR, which similarly inhibited OxPC-induced myosin light chain phosphorylation in cultured human airway smooth muscle cells. In summary, OxPC mediates airway narrowing by triggering TRPA1 and RyR-mediated mobilization of intracellular and extracellular Ca in airway smooth muscle. These data suggest that OxPC in the airways of allergen-challenged subjects and subjects with asthma may contribute to airway hyperresponsiveness.